Algal Blooms Sweden - 2021 - Tronholm, Ana; Lindeberg, Magnus; Germishuys, Jurie (University of Gothenburg, 2023)
Dataset containing images of algal blooms in the Baltic Sea. The data is provided with a metadata description containing time spotted, comments, municipality, county and coordinates of each image. The images and metadata file are archived in a zip package. Images show various summer surface accumulations of so-called harmful algal blooms (HABs) or nuisance blooms. Typically, these blooms consists of species of cyanobacteria of the order of Nostocales, including toxic Nodularia and Aphanizomenon. These blooms were verified by Informationscentralen (Länsstyrelsen Stockholm and Länsstyrelsen Västerbotten). However, the blooms seen in the images have not been taxonomically annotated by microscopy nor genetic analysis.

The following data fields are contained in the metadata files (provided in both json and csv format):

report_id: unique identifier for reporting record, type: string
time_spotted: date that bloom was spotted, type: datetime
algae_overview_photo: url to overview photo submitted, type: string
algae_detail_photo: url to detailed photo submitted, type: string
comments: Any additional information relating to the bloom, type: string
lat: Latitude of position where bloom was seen, type: float
long: Longitude of position where bloom was seen, type: float
place: County where bloom was spotted, type: string
kommun: Municipality where bloom was spotted, type: string

Total observations: 251
Notes: Not every observation has an accompanying image and others were verified using other information provided.
One of the submitted photographs for 2021 contained unintentionally collected personal data. It has been excluded from this dataset to make open data publishing possible.

Dataset som innehåller bilder av algblomning i Östersjön. Uppgifterna är försedda med en metadatabeskrivning som innehåller tidpunkt, kommentarer, kommun, län och koordinater för varje bild. Bilderna och metadatafilen arkiveras i ett zip-paket. Bilderna visar olika sommarytansamlingar av så kallade skadliga algblomningar (HAB) eller störande blomningar. Vanligtvis består dessa blomningar av arter av cyanobakterier av ordning Nostocales, inklusive de giftiga Nodularia och Aphanizomenon. Dessa blomningar har verifierats av Informationscentralen (Länsstyrelsen Stockholm och Länsstyrelsen Västerbotten). Blomningen som syns på bilderna har dock inte fastställts taxonomiskt genom mikroskopi eller genetisk analys.

Följande datafält finns i metadatafilerna (tillhandahålls i både json- och csv-format):

report_id: unik identifierare för rapporteringspost, typ: textsträng
time_spotted: datum då blomningen sågs, typ: datetime
algae_overview_photo: url till översiktsfoto inskickad, typ: textsträng
algae_detail_photo: url till detaljerat foto skickat, typ: textsträng
kommentarer: All ytterligare information som rör blomningen, typ: textsträng
lat: Latitud för position där blomningen sågs, typ: float
long: Longitud för position där blomningen sågs, typ: float
plats: Län där blomning sågs, typ: textsträng
kommun: Kommun där blomningen sågs, typ: textsträng

Totalt antal observationer: 251
Obs: Alla observationer har inte en tillhörande bild och andra har verifierats med hjälp av annan information som tillhandahålls.
Ett inrapporterat fotografi för 2021 hade oavsiktligt insamlad persondata i sig och detta har därför exkluderats ur detta dataset för att möjliggöra publicering av öppna forskningsdata.
Algblomningar Sverige - 2021
Keywords: Harmful Algal Bloom; Skadlig algblomning; algal bloom; citizen science; procaryote; cyanobacteria; Species distribution; Arters utbredning; baltic sea; nostocales; Ecology; Ekologi; Biota; Biologi och ekologi; Oceans; Kust och hav; Environment; Miljö